A Potential Framework for Allocating National Park Service Budgets - Rideout, Douglas B.; Wei, Yu; Kernohan, Nicole; Kirsch, Andy G. (Frontiers in Forests and Global Change, 2022)
The US Department of Interior, including the National Park Service (NPS), has interest in developing a national fire budgeting process that reflects and promotes program (fuels and preparedness) efficiencies while being transparent, fair, stable, and predictable. A systematic approach should have the potential to operate at all scales (national, regional, and park). To accomplish these objectives, the research introduced a Budgeting Analysis that can be integrated into the STARFire (Strategic budgeting and planning system for wildland fire). The approach used is known as the “gradient method” reflecting the concept that budgets are allocated based on proportionate performance. Using the gradient method, budget increments were allocated to fuels and preparedness programs to improve return on investment (ROI). Three-dimensional performance surfaces were generated for each of the parks in the NPS’s Alaska Fire Management Zone and a gradient was fit to each surface. The individual park gradients were then used to allocate the zone budget increments to the parks and in turn, to the park’s fuels and preparedness programs. These allocations were then summed up to illustrate regional and park level allocations and allocations by program. The results show how a full range of budget increments can be allocated from the zone to each individual park and to each park’s program. The process and the allocations are repeatable and defensible while meeting the NPS budgeting criteria. They also address the concerns expressed by the US Government Accountability Office and reflect the objectives of the Cohesive Strategy. In the current study, we demonstrate a pragmatic example of implementing this method.